2023
DOI: 10.1029/2022gb007607
|View full text |Cite
|
Sign up to set email alerts
|

Global Riverine Export of Dissolved Lignin Constrained by Hydrology, Geomorphology, and Land‐Cover

Abstract: The land‐to‐ocean export of terrestrial dissolved organic matter (tDOM) links the two largest organic carbon (OC) pools on Earth and is changing due to anthropogenic activity and climate change. Lignin phenols are often utilized as diagnostic markers for tDOM in aquatic systems, but information on the global dissolved lignin flux is still uncertain as linkages between future changes in export and global changes are poorly constrained. Thirty‐two new measurements from 15 Chinese rivers and 548 measurements coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 78 publications
(235 reference statements)
0
1
0
Order By: Relevance
“…It was found that the molecular composition of DBC FT , especially the nitrogen content, was affected by agriculture coverage (Wagner et al 2015). Although covering a whole hydrograph, differences in agricultural coverage between the Chanjiang (the primary freshwater source in the study area) and the North Jiulong River (used for comparison) may bias the identification of river-derived formulae, especially those nitrogen-containing compounds (Bao et al 2023b). Other factors to consider include the possibility that the same formulae may represent different compounds with diverse structures and that some formulae found in rivers or aerosols may also come from unidentified sources.…”
Section: Molecular Composition Of Dbc Ft : Sources and Influencing Fa...mentioning
confidence: 99%
“…It was found that the molecular composition of DBC FT , especially the nitrogen content, was affected by agriculture coverage (Wagner et al 2015). Although covering a whole hydrograph, differences in agricultural coverage between the Chanjiang (the primary freshwater source in the study area) and the North Jiulong River (used for comparison) may bias the identification of river-derived formulae, especially those nitrogen-containing compounds (Bao et al 2023b). Other factors to consider include the possibility that the same formulae may represent different compounds with diverse structures and that some formulae found in rivers or aerosols may also come from unidentified sources.…”
Section: Molecular Composition Of Dbc Ft : Sources and Influencing Fa...mentioning
confidence: 99%